Suicide cases investigated at the state mortuary in Bloemfontein, 2003–2007 - Karen Stark; Gina Joubert; Magdalena Struwig; Marinus Pretorius; Nak van der Merwe; Henmar Botha; Jaco Kotzé; Daniel Krynauw (South African Family Practice)
Background: Up to 8 000 South Africans commit suicide annually. This study aimed to investigate the profile of suicide cases in Bloemfontein and the southern Free State province.